Potret Pemanfaatan YouTube dalam Pemerolehan Bahasa Kedua Anak di Lingkungan Sekolah dan Keluarga - Aisyah Aisyah; Kholik Kholik (Institut Agama Islam Sunan Giri Ponorogo, 2026)
This study aims to provide an in-depth look at the use of YouTube in second language acquisition among children in school and family environments, and to identify the contributions and barriers arising from differences in regulations across the two environments. The research employs a qualitative, descriptive approach. Subjects were selected using a purposive sampling technique, comprising 10 children aged 7 to 12 years. The research was conducted in Mulyosari Village, Gedangan, Malang Regency. Data collection and instruments utilized data triangulation techniques consisting of three stages: observation, in-depth interviews with parents and teachers, and documentation in the form of audio/video recordings. Data analysis followed the Miles and Huberman model, which includes three main stages: data reduction, data display, and conclusion drawing. The results indicate that YouTube functions as a “virtual classroom” that naturally triggers second-language acquisition, specifically English vocabulary, through its content. Furthermore, the study identified a disconnection between the home and school environments. In contrast, unrestricted access at home allows children to become fluent in popular terms, whereas formal and instructional rules restrict their use at school. Additionally, children's pronunciation tends to be merely imitative, lacking a deep understanding of intonation and meaning, which often leads to ineffective communication.